Influence of tow duration on catch performance of trawl survey in the Mediterranean Sea - Sala, Antonello (PLoS One, 2018)
The aim of this study was to assess the effect of tow duration on catch per unit of swept area (CPUE), trawl catch performance, and the proportion of the species caught in a trawl survey. Longer tows are expected to have a greater probability of catching species. An average of 26 species were caught in the first 30 minutes, whereas only about one additional species was caught in the next 30 minutes in longer tows. The shorter tows involved a decrement in catch weight for 11 of the 12 target species sampled, demonstrating that tow duration did affect catch per unit of swept area CPUE. The shorter tows were associated with a significant reduction of the overall CPUE in terms of weight of the main target species and of the total catch (circa 60%). The same strong reduction of around 70% was found in particular for European hake (Merluccius merluccius) and surmullet (Mullus spp) and 50% for Nephrops (Nephrops norvegicus). The shorter tows were less efficient in catching large-sized hake, surmullet, Nephrops, Atlantic horse mackerel (Trachurus trachurus), and poor cod (Trisopterus minutus), even though the difference was significant only for Nephrops. Regardless of the p-value statistic, these findings suggest that the continuity of survey time series would be severely impaired by changing tow duration. Further work is required to explore a way to reduce tow duration without reducing CPUE.